Negative association between plasma cortisol levels and aggression in a high-risk community sample of adolescents - Poustka, Luise; Maras, Athanasios; Hohm, Erika; Fellinger, Johannes; Holtmann, Martin; Banaschewski, Tobias; Lewicka, Sabina; Schmidt, Martin H.; Esser, Günter; Laucht, Manfred (Journal of neural transmission, 2010)
In this study, the association of aggressive behavior and personality traits with plasma cortisol levels was investigated in a high-risk community sample of adolescents. Plasma cortisol levels were collected in 245 fifteen-year-olds (118 males, 127 females) from an epidemiological cohort study of children at risk for psychopathology. Additionally, measures of reactive and proactive aggression, externalizing behavior and callous-unemotional together with impulsive personality features were assessed. Both subtypes of aggression as well as delinquent behavior and impulsive personality traits showed significant negative correlations with plasma cortisol levels. This association was observed in males, but not in females. In both gender groups, callous-unemotional traits were unrelated to plasma cortisol levels. This result suggests that the association between cortisol levels and aggression in adolescents is mediated rather by impulsivity than by unemotional or psychopathic traits.